Exploring the Role of English Japanese-Style in a Japanese Drama: Gairaigo and Wasei-Eigo - Pratiwi, Dinda Ayu (Language Horizon: Journal of Language Studies, 2023)
This study aimed to look into the roles of Gairaigo and Wasei-Eigo in Japanese and how the localization process occurs when two languages’ terms change. Some theories were used in this study, including Japanese Katakana, Gairaigo types by Ishiwata (2001) and Shibatani (2001), and Katakana Transformation by Kawarazaki (2004). The data was acquired in the form of words and phrases from a dialogue between characters in the Japanese drama Watashitachi wa Douka Shiteiru. The descriptive qualitative method was utilized, as stated by Miles and Huberman (2014). The documentation technique was used since it corresponded to subtitles in the drama. The findings of this study demonstrated that, in addition to modernism and informal connotation, Japanese loanwords performed other functions in Japanese, such as acting as a lexical gap filler and efficiency in written or spoken Japanese. Furthermore, the process of localization affects not only phonology but also morphology, as some of them might be introduced by Japanese suffixes. Thus, the Japanese loan words are not just translations because understanding these two issues requires considerable Japanese language skills, particularly knowledge of the Katakana writing system. As a result, noticing the discrepancies while they are going through the localization process would be easier.